Knowledge Level of Farmers regarding the Use of Pesticide for Pest and Disease Control - Sandy, Yohana Avelia; Zahro, Frelyta Ainuz; Rizky, Dewi Ratih; Fajarwati, Santi Kusuma; Effendi, Mokhtar (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
Farmers' utilization of pesticides in Indonesia is very high because pesticides are the main method for farmers to control pests and diseases. This research was conducted to determine farmers' level of knowledge of the use of pesticides. The research method used in this research was quantitative, using survey methods. The survey method was used to obtain factual information by exploring the level of knowledge, attitudes and actions of farmers related to pesticides. Sampling was conducted in Tulungrejo Village, Ngantang District, Malang Regency, with 50 farmers as respondents. The results of this study found that most of the respondents know about pesticides and the types of pesticides. The primary factor influencing pesticide use selection was the characteristics of farmers. The farmer age in Tulungrejo Village is 56%, and the farmer is 30-50 years old. Most of them had a low educational level, and 48% of the farmers only finished elementary school. However, the respondents needed to learn that the use of pesticides should be the last step in controlling pests and diseases, according to Integrated Pest Management (IPM). Therefore, an education and training program on IPM and pesticide use should be planned to assist farmers in improving their knowledge and skills.